Development of an observational measure of social disinhibition after traumatic brain injury. Issue 3 (15th March 2016) - Osborne-Crowley, Katherine; McDonald, Skye; Francis, Heather
ABSTRACT: Introduction : This study aimed to validate a new observational measure of socially disinhibited behavior for use in a population of individuals with traumatic brain injury (TBI). Method : Participants were twenty-two adults with severe TBI (mean age = 50.45 years) and 21 healthy comparison participants (mean age = 45.29 years). Ratings of observed social disinhibition were correlated with the disinhibition domain scores of the Neuropsychiatric Inventory–Disinhibition (NPI–D) and with Sydney Psychosocial Reintegration Scale (SPRS) scores. A regression analysis was undertaken to determine whether formal measures of disinhibition could predict observed disinhibition. Results : The interrater absolute agreement for the social disinhibition ratings was good, intraclass correlation coefficient (ICC) = .69. Participants with TBI were rated as significantly more disinhibited than comparison participants, t (25.05) = –2.07, p = .049. The ratings were positively correlated with the NPI frequency score ( r = .45, p = .038) and distress score ( r = .45, p = .035). The ratings were not related to change in employment or in interpersonal relationships on the SPRS, and formal measures of disinhibition were unable to predict observed social disinhibition. Conclusions : This study demonstrates good interrater reliability and construct validity of the observational measure. The results evidence the usefulness of this measure and the NPI–D for detecting social disinhibition after TBI.